KUALITAS PEMBELAJARAN DAN KEPEMIMPINAN WALI KELAS MENDUKUNG EFEKTIVITAS BELAJAR SISWA - Balthasar Watunglawar (SOSCIED, 2020)
The purpose of this research is toanalyze, explain, and discuss how to create qualified formal learning in support of students' self-learning effectiveness, how the leadership style of Guardian Class in supporting the effectiveness of self-learning of students, and factors influence the effectiveness of student self-learning. The research is designed to answer the problems and objectives that have been formulated and proposed. To address the problems and objectives, the researchwas conducted in IMPRES Elementary School 102 Sorong City Klagete, West Papua. To answer the research problem, this research uses qualitative method, where data collected and analyzed, obtained by observation, interview, and documentation. The data obtained were analyzed by reducing, presented and summarized.The results ofthis study states that this study mentioned to improve the effectiveness of formal learning, it is necessary to structuring the quality of formal learning. The education process should be done regularly, systematically, by following clear requirements. Teachers must be creative using a variety of techniques and teaching methods that are contextual to the situation and students' absorption. In addition, it needs to be supported with the leadership qualities of the Guardian Class. The ability of the Guardian Class in communicating, motivating students, visionary is very helpful in improving the quality of formal learning of students.The family environment factors, peers, study time, teacher's knowledge and skills, guardian's attention, and coorporative learning are very important to be observed and arranged well. All should be considered in improving the management of education and the formulation of school policies in the effort of improvement and improvement of quality.